ANALISIS PENGUNGKAPAN LAPORAN KEUANGAN PERUSAHAAN PEMBIAYAAN - Oktaviani, Intan Herlina; Martani, Dwi (Jurnal Akuntansi dan Keuangan Indonesia, 2006)
The aims of the research is to provide empirical evidence about financial statement disclosures of multifinance companies and the factors that determines the disclosure level. The multifinance companies are unique industries because there have various product of financing like leasing, installment sales and borrowing. fhe research examines disclosure level of multifinance company that listed in the database Directorate General Financial Institutions, Ministry of Finance. We use financial statement in 2003 and 2004. The research use the regulation of Directorate General Financial Institution number 1500/2005, financial accounting standard for leasing and factoring as a disclosure guideline, because there is no specific standard or Bapepam disclosure guideline for multifinance industry. The results indicate that disclosure level of multifinance company is 78,35% in 2004. There is increasing about 1.21% compare to the disclosure level in 2003. There is significant differentiation of disclosure level between status of company and size of firm but no significant differentiation between size of auditor. The result using linear regression show that disclosure level is influenced by profitability, company status, size of the firm and size of auditor.